(untitled) (Journal of Science and Technology, 2016)
The purpose of this study was to investigate the effects of radiations on the ocular health of welders and to determine the prevalence of ocular diseases among them in the Kumasi metropolis. In this study, 470 welders (test group) and 450 non-welders (control group) at Suame “Magazine” in the Kumasi metropolis were enrolled for the study. Methods employed in the examination were the administration of a questionnaire seeking clinical and ocular history, visual acuity measurements, external eye examination and ophthalmoscopy. Where necessary, referrals were written for patients to the Komfo Anokye Teaching Hospital (KATH) for further examination and treatment. Two hundred and forty two welders, (51.1%) had worked for a period of over ten years. The chief ocular complaints found amongst the respondents were gritty sensation (65.1%) and excessive tearing (56.0%). The commonest radiation-related ocular diseases were pterygium (56.6%), photoconjunctivitis (22.6%) and cataract (5.1%) whereas in the control group the commonest conditions were pterygium (6.2%), pinguecula (2.2%) and cataract (1.3%). There was a small number of retinopathies associated with radiation (4.0%). Most (60.0%) of the welders used electricity (arc welding) and the remaining (40.0%) used carbide (oxy-acetylene flame). A total of 308 ( 65.5%) welders and 76 (16.9%) non-welders (control group) had one or more ocular conditions. The prevalence of eye diseases among the welders and control group is thus 65.5% and 16.9% respectively. In conclusion, it was seen that the ocular symptoms and ailments prevalent among the welders were most likely due to the radiations they are exposed to in their work environment.